2012
DOI: 10.1111/ppa.12012
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a wheat cultivar mixture against splash‐dispersed septoria tritici blotch epidemics

Abstract: The use of cultivar mixtures to control foliar fungal diseases is well documented for windborne diseases, but remains controversial for splash-dispersed diseases. To try to improve this strategy, a cultivar mixture was designed consisting of two wheat cultivars with contrasted resistance to Mycosphaerella graminicola, responsible for the rainborne disease septoria tritici blotch (STB), in a 1:3 susceptible:resistant ratio rather than the 1:1 ratio commonly used in previous studies. The impact of natural STB ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 43 publications
(69 reference statements)
12
45
1
Order By: Relevance
“…Current mitigation techniques of foliar diseases, such as the intensive use of chemicals or genetically modified organisms, can be complemented by polyculture [13,75,76] or integrated culture [77]. Our work has shown how both impact speed and distance from an edge shape the statistics of ejected droplets upon raindrop impact.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Current mitigation techniques of foliar diseases, such as the intensive use of chemicals or genetically modified organisms, can be complemented by polyculture [13,75,76] or integrated culture [77]. Our work has shown how both impact speed and distance from an edge shape the statistics of ejected droplets upon raindrop impact.…”
Section: Discussionmentioning
confidence: 81%
“…Rain was found to be correlated with the dispersal of foliar diseases such as Septoria leaf blotch and Fusarium head blight, affecting wheat and rice, respectively [8][9][10]. Prior studies mainly focused on dispersal statistics collected at the level of crop fields or parcels [9,[11][12][13]. Investigations at the level of leaf and plant remain scarce [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, STB severity in cultivar mixtures is moderately reduced compared to the expectation based on the severity in the pure stands, although Cowger & Mundt (2002) did not observe a consistent pattern. In particular, Gigot et al (2013) found that a susceptible cultivar was consistently protected in a mixture under low to moderate STB levels. Subsequent greenhouse experimentation (Vidal et al, 2017) and a modelling study (Vidal et al, 2018) have demonstrated the importance of canopy structure for the efficacy of a mixture.…”
Section: Introductionmentioning
confidence: 98%
“…Cultivar mixtures suppress the development of disease epidemics when the mixture components have contrasting levels of resistance to the targeted disease (Wolfe, 1985;Finckh & Wolfe, 2006;Gigot et al, 2013). Consequently, most studies investigated mixtures of disease-susceptible and diseaseresistant cultivars (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation